Deciding on the most suitable teaching method in the mathematics classroom - Serin, Hamdi (Opción, 2019)
In this research conducted with 35 mathematics teachers selected by stratified co-probative sampling method, the use of teaching methods/approaches and techniques that mathematics teachers used in their lectures were examined and tried to determine their opinions about the application in mathematics teaching. As a result, most of the mathematics teachers who participated in the research do not use games, case studies and problem-solving. In conclusion, the work of observing and rearranging the curriculum should be based on the mental and physically active participation of the students in the mathematics learning process